Antiques bizarre [large type] - Allan, Barbara (Allan, Barbara. Trash 'n' treasures mystery., 2010)
While dealing with morning sickness, her bipolar mother, and the citywide antiques bazaar, Brandy Borne must also deal with murder when a ninety-year-old Russian widow donates a priceless antique that is not what it seems.